Structure and dynamics of bound water in poly(ethylene-vinylalcohol) copolymers studied by terahertz spectroscopy. (18th July 2018) - Hoshina, Hiromichi; Iwasaki, Yoh; Katahira, Eriko; Okamoto, Makoto; Otani, Chiko
Abstract: Poly (ethylene-vinylalcohol) copolymer (EVOH) films under different humidity conditions were studied by THz absorption spectroscopy to obtain information about the bound water. An intermolecular stretching mode of bound water was observed at around 6 THz, similar to that in liquid water; and the very weak libration mode indicates that this water is frozen. By generalized two-dimensional correlation spectroscopy (2DCOS) and perturbation-correlation 2D moving window (PCMW2D) correlation spectroscopy, the bound water was categorized into three types: frozen with amorphous structure (I), liquid-like with librational motion (II), and nearest neighboring water with weaker hydrogen bonding network (III). The strongly inhomogeneous intermolecular stretching band of water I shows that the frozen bound water is amorphous. The frequency shift of this band in water III indicates a weaker hydrogen bonding network around the ethylene group. Changes in the films' oxygen permeability are discussed and correlated with the dynamics of bound water. Graphical abstract: Image 1 Highlights: THz absorption spectroscopy used to measure bound water in hydrated EVOH films. The bound water showed intermolecular stretching mode but no librational mode. The bound water was categorized into three types by 2DCOS and PCMW2D analysis.